Photoluminescence Quenching of Nanocomposite Materials Used for Organic Solar Cells - Thao, Tran Thi; Chung, Do Ngoc; Dinh, Nguyen Nang; Truong, Vo Van (Communications in Physics, 2014)
In this work, we have studied the photoluminescence (PL) quenching of two polymeric composites, poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) and poly(3-hexylthiophene) (P3HT) in presence of nc-TiO\(_{2}\) particles by PL- spectroscopy. PL quenching values are 19.2\(\text{%}\) and 45.5\(\text{%}\), for MEH-PPV+nc-TiO\(_{2}\) and P3HT+nc-TiO$_{2}$, respectively. The obtained results on the relationship of PL quenching and photoelectrical efficiency (PCE) of an OSC showed that the quenching coefficient of a semiconducting polymer can be considered as apreliminarycriterion for choosing an appropriate polymeric composite being used for OSC preparation. Under illumination of solar energyof 56 mW/cm\(^{2}\), P3HT+TiO\(_{2}\) based OSC possess FF, V$_{OC}$, J$_{SC}$ and PCE of 0.64, 0.243 V, 1.43 mA/cm\(^{2}\) and 0.45\(\text{%}\), respectively